Brain atrophy following hemiplegic migraine attacks. (May 2018) - Pelzer, Nadine; Hoogeveen, Evelien S; Ferrari, Michel D; Poll-The, Bwee Tien; Kruit, Mark C; Terwindt, Gisela M
Background: Patients with hemiplegic migraine (HM) may sometimes develop progressive neurological deterioration of which the pathophysiology is unknown. Patient: We report a 16-year clinical and neuroradiological follow-up of a patient carrying a de novo p.Ser218Leu CACNA1A HM mutation who had nine severe HM attacks associated with seizures and decreased consciousness between the ages of 3 and 12 years. Results: Repeated ictal and postictal neuroimaging revealed cytotoxic oedema during severe HM attacks in the symptomatic hemisphere, which later showed atrophic changes. In addition, progressive cerebellar atrophy was observed. Brain atrophy halted after cessation of severe attacks, possibly due to prophylactic treatment with flunarizine and sodium valproate. Conclusion: Severe HM attacks may result in brain atrophy and prophylactic treatment of these attacks might be needed in an early stage of disease to prevent permanent brain damage.